2017
DOI: 10.3389/fpls.2017.00911
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock Sub-Optimal Temperature Tolerance Determines Transcriptomic Responses after Long-Term Root Cooling in Rootstocks and Scions of Grafted Tomato Plants

Abstract: Grafting of elite cultivars onto tolerant rootstocks is an advanced strategy to increase tomato tolerance to sub-optimal temperature. However, a detailed understanding of adaptive mechanisms to sub-optimal temperature in rootstocks and scions of grafting combinations on a physiological and molecular level is lacking. Here, the commercial cultivar Kommeet was grafted either onto ‘Moneymaker’ (sensitive) or onto the line accession LA 1777 of Solanum habrochaites (tolerant). Grafted plants were grown in NFT-syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 77 publications
(123 reference statements)
1
25
0
Order By: Relevance
“…Although the effects of different rootstocks on grafting have been well studied, the mechanism leading to this differential development is not clear. With the explosion in second-generation sequencing technology, to obtain insight into potential mechanisms underlying the influence of rootstock on scion growth, transcriptome studies have increasingly been used to decipher the molecular mechanisms that lead to this difference [6][7][8][9][10][11]. Different rootstocks were found to significantly affect the expression of genes involved in the auxin signal transduction pathway and gibberellic acid (GA) biosynthesis pathway in grafted plants and regulated hormone levels and their signaling pathways [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of different rootstocks on grafting have been well studied, the mechanism leading to this differential development is not clear. With the explosion in second-generation sequencing technology, to obtain insight into potential mechanisms underlying the influence of rootstock on scion growth, transcriptome studies have increasingly been used to decipher the molecular mechanisms that lead to this difference [6][7][8][9][10][11]. Different rootstocks were found to significantly affect the expression of genes involved in the auxin signal transduction pathway and gibberellic acid (GA) biosynthesis pathway in grafted plants and regulated hormone levels and their signaling pathways [8].…”
Section: Introductionmentioning
confidence: 99%
“…The higher dry matter content in the montane ecotype may also be related to a higher cold tolerance for this ecotype compared to that originating from a coastal location. Indeed, a higher tolerance of plants to sub-optimal temperatures is associated with a higher dry matter percentage originating mainly from increased starch accumulation (Venema et al, 1999; Król et al, 2015; Ntatsi et al, 2017b). On the other hand, a low dry matter content in leaves may be a consequence of increased leaf succulence, which is an adaptive morphological characteristic of plants to salinity (Greenway and Munns, 1980; Shabala, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SUSY has been shown to interact with multiprotein complex involved in cellulose/callose biosynthesis in main crops such as cotton, tobacco, and wood (Nakai et al, 1999, Persia et al, 2008, Coleman et al, 2009, Fujii et al, 2010). Interestingly, Ntatsi et al (2017) reported an increase in expression of genes related to cellulose biosynthesis in the rootstock of cold tolerant tomato Solanum habrochaites LA1777 when grown at suboptimal root temperature of 15°C, whereas in the same growth temperature those genes were not up-regulated in the rootstock of cold sensitive tomato Moneymaker. Therefore, SUSY and other players involved in sucrose metabolism would be of interest for further investigation.…”
Section: Discussionmentioning
confidence: 99%